A ghost travels through Peru: Escalas from spectral criticism - Antonio Mazzotti, José (2023)
The constant appearance of ghosts and doubles throughout Escalas, the first book in prose by César Vallejo, published in March 1923 and made up of twelve reflective, poetic and narrative texts, leads us to think about the need for an explanation beyond the recognizable influences from Gothic literature and Modernism. The ghosts in Vallejo would reveal a social and historical tension that appears in a veiled way and that says a lot about the poet’s conscience through the analysis of spectral criticism. This article investigates this contextual reading in order to illuminate aspects of the work that have not been examined until now.